Agricultural Policy: Systematic Literature Review - Nasution, Faiz Albar; Fahreza, Imam; Thamrin, Muhammad Husni (Journal of Peasants' Rights, 2023)
In general, agriculture is a neutral sector in a country. In this case, many countries rely on the agricultural sector, where agriculture is the primary production in economic development, often referred to as agrarian countries. The main objective of agricultural policy is to maintain agricultural production by achieving economic benefits compatible with poverty reduction as a final reaction to meet the population's social needs with the least possible impact. Seeing the problems and opportunities in the agricultural sector that also have socio-political impacts, this research is vital to understanding the implications and implementation of agricultural policies. This research uses a bibliometric analysis method to see the research development with the keyword "agriculture policy" on Google Scholar search with a vulnerable time in 2020-2023, which produces data for as many as 155 articles. The results show that the publication trend regarding "agriculture policy" has critical players who are relevantly attracting scientists to study by looking at the trend of keywords that most often come out, making discussions about agricultural policy a form of literature that can be a reference or consideration in policy making. Thus, food policy research must also continue to be carried out to obtain new knowledge as a reference in advancing agriculture in the scope of science.